Layanan data dan informasi dalam rangka meningkatkan layanan di perpustakaan perguruan tinggi - Ratnaningsih Ratnaningsih; Abdul Rahman Saleh (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2017)
In order to meet the users’ needs, the university library needs to improve the quality of its services. The university libraries have a group of the users to be served such as: 1) university leaders 2) lecturers 3) student 4) others (administratif staff and external readers). So far, the university library services only focus student and lecturer, focusing on circulation services and provide documents which is need by users, while the group of leaders has not been served well their information needs. Fankly speaking, the library can play a role in providing information services to the group of leaders to support the decision-making and daily operational tasks. The information that could be given to the group of leaders is the result of data and information analysis from the library collections such as student report, thesis, dissertation and research report. This study will discuss about the library opportunities to perform data and information analysis. Mapping the ability or competence of the librarians that must be mastered in order to be able to undertake that activity that is to serve the group of university leader will be analyzed. This study is a qualitative descriptive study. Interview will be conducted to informant. Determination of informants will be done by snowball sampling. Interview results will be analyzed by descriptive analysis. The results of this study are expected to provide recommendations to librarian leaders and librarians throughout the university library.